DESIGN OF A SIMPLE MUFFLE FURNACE FOR TEMPERATURE OPTIMIZATION IN ASH CONTENT ANALYSIS - Abadi, Farid R. (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2018)
Analysis of the ash content in biomass conducted through the incineration process in the muffle furnace at a given temperature of 575+25oC. The result depends on the accuracy level on the temperature sensor in the muffle furnace. It was attempted to achieve the optimum temperature and to detect the muffle furnace temperature by installing the thermocouple sensor type K directly Â the porcelain sample plate. It yielded that by direct incineration process and gradual process the setup point reached in 60-90 minutes and 150-180 minutes before attaining the steady temperature, respectively. The temperature distributed uniformly for all treatments at + 6.61 oC. The temperature measurement accuracy was + 1.18%, and the overall temperature gradient was + 28.69 oC. Moreover, there was no difference in the temperature fluctuation among the treatments at the temperature ofÂ + 20.95 oC. The optimum temperature of the chamber was Â 588 oC for analyzing ash content of biomass.